Impact of hearing loss on cognitive function in community-dwelling older adults: serial mediation of self-rated health and depressive anxiety symptoms - Chen, Fenghui; Chen, Yingying; Jiang, Xin; Li, Xiaoyang; Ning, Hongting; Hu, Mingyue; Jiang, Wenxin; Zhang, Nan; Feng, Hui; Yan, Ping (Frontiers in Aging Neuroscience, 2023)
Background Hearing loss can exacerbate cognitive decline; therefore, exploring the mechanisms through which hearing loss affects cognitive function is crucial. The current study aimed to investigate the impact of hearing loss on cognitive function and the mediating role played by self-rated health and depressive anxiety symptoms. Methods Using stratified whole-group random sampling, the study employed a cross-sectional design and included 624 participants aged ≥65 years from three communities in Urumqi, China. Cognitive function was assessed using the Mini-Mental State Examination. Hearing function and self-rated health were determined by self-report. The 15-item Geriatric Depression Scale and the 7-item Generalized Anxiety Disorder Scale were used to assess depressive anxiety symptoms. Serial mediation analysis was performed using AMOS 26.0. Results Hearing loss can not only negatively affect cognitive function in older adults directly (direct effect = −0.106; SE = 0.045; 95% confidence interval (CI): −0.201 to −0.016), but also indirectly affect the relationship between hearing loss and cognitive function through self-rated health and depressive anxiety symptoms. The results of the serial mediation analysis showed that the total indirect effect of self-rated health and depressive anxiety symptoms was −0.115 (95% CI: −0.168 to −0.070), and the total effect of the model was −0.221 (95% CI: −0.307 to −0.132), with the total indirect effect accounting for 52.04% of the total effect of the model. Conclusion Our study discovered that there is a partial mediation of the relationship between hearing loss and cognitive function by self-rated health and depressive anxiety symptoms. It is suggested that by enhancing self-rated health and ensuring good mental health, the decline in cognitive function among older adults with hearing loss can be delayed.